The Strategy of Poor Students Dealing with The Home-Learning System - Martono, Nanang; Naura, Nabilla Khansa; Isnania, Rahma; Lisnawati, Lisnawati; Nugraheni, Rakhma (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
This paper describes the strategy of poor students dealing with the home-learning system in the time of COVID-19. The home-learning system, however, theoretically generates the digital divide for the majority of poor students because they have less capital and resources. In order to be involved in the system, they have to afford themselves in getting the digital devices, such as smartphones and laptop. It uses the qualitative method undertaken in four regencies: Banyumas, Purbalingga, Banjarnegara, and Tegal. The poor students who undergo the home-learning system in those regencies are enlisted to be purposive samples. The profile is selectively included because of their lack of means in dealing with the system. For this study, we analyze the data collected from in-depth interviews, observation, documentation, followed by constant comparative analysis. The result indicates that most poor students only have the worksheets (LKS) and books as their primary learning resources. The poor students cannot optimally undergo the system due to the financial constraints which lead to the shortage of use of technology. Also, the intensity of parental participation during school hours is low due to their educational background and working hours. The condition is also worsened by the absenteeism of the teacher.